Mining RDF metadata for generalized association rules: Knowledge discovery in the semantic web era - JIANG, Tao (Institutional Knowledge at Singapore Management University, 2006)
In this paper, we present a novel frequent generalized pattern mining algorithm, called GP-Close, for mining generalized associations from RDF metadata. To solve the over-generalization problem encountered by existing methods, GP-Close employs the notion of emphgeneralization closure for systematic over-generalization reduction.